2012
DOI: 10.1186/1471-2318-12-8
|View full text |Cite
|
Sign up to set email alerts
|

The impact of early emergency department allied health intervention on admission rates in older people: a non-randomized clinical study

Abstract: BackgroundThis study sought to determine whether early allied health intervention by a dedicated Emergency Department (ED) based team, occurring before or in parallel with medical assessment, reduces hospital admission rates amongst older patients presenting with one of ten index problems.MethodsA prospective non-randomized trial in patients aged sixty five and over, conducted in two Australian hospital EDs. Intervention group patients, receiving early comprehensive allied health input, were compared to patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 28 publications
0
57
0
Order By: Relevance
“…Other patient populations have benefited from specialized emergency services, including psychiatric and geriatric patients; however, little has been done thus far with complex surgical populations. (2427) The challenge moving forward is to determine if the present costs and clinical outcomes associated with recipient ED care are such that they warrant redesign of the acute recipient assessment and management. For a subset of recipients, ED care is certainly the best option as it allows for rapid, effective triage and management of post-surgical emergencies.…”
Section: Discussionmentioning
confidence: 99%
“…Other patient populations have benefited from specialized emergency services, including psychiatric and geriatric patients; however, little has been done thus far with complex surgical populations. (2427) The challenge moving forward is to determine if the present costs and clinical outcomes associated with recipient ED care are such that they warrant redesign of the acute recipient assessment and management. For a subset of recipients, ED care is certainly the best option as it allows for rapid, effective triage and management of post-surgical emergencies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the effectiveness of a team of allied health professionals offering co-ordinated care to older people in EDs (similar to our rapid assessment teams) found a very small reduction in emergency admissions albeit using a non-randomised design. 59 The use of geriatric assessment in an ED (a type of senior review initiative) identified a lower conversion rate to admission, again using a non-randomised design. 60 However, it is important to evaluate robustly some of the types of schemes discussed in our study, using randomised controlled designs if possible.…”
Section: Effective Interventions For Reducing Emergency Admissionsmentioning
confidence: 99%
“…Although no significant difference in number of emergency admissions at 30 days (P = 0.312).No significant difference in visits to ED (without admission) within 30 days (p = 0.349)Assessments post intervention not blinded. Some control group patients may have had CGA from another service.Arendts et al, 2012, Australia [7]Patients ≥65 yrs presenting to two EDs with one of the ten presenting complaints often resulting in admission (UTI, respiratory tract infection, fall with minor injury, hip/knee pain, back pain, heart failure, angina, syncope, TIA, new confusion/delirium). Patients requiring urgent medical treatment were excluded.Non-randomised controlled clinical trial.…”
Section: Methodsmentioning
confidence: 99%